Thado Bhaka: A Source of Social Intercourse - Dura, Yam Bahadur; Neupane, Binod (Marsyangdi Journal, 2022)
Thado bhaka is one of the popular genres of folk songs in the Gandaki region. The territory of the Gandaki region is extended from Budhigandaki in the east to Kaligandaki in the west. Thado bhaka is the diminishing musical genre. The habitual and experienced performers of thado bhaka are dying out. These days a handful of people from the old and new generations are capable of performing it. This article aims at introducing thado bhaka connecting it to its history, nature, and style. Observation, interview and secondary sources were used to collect information for this study. It is found that thado bhaka has a typical tune, language, style and meaning and become an identity of the Dura people of the Gandaki region. However, the study has pointed out some influences on its originality because of the growing wave of modernisation, especially after the development of electronic instruments.